Respuesta :
Answer: The simplified expression is: " 5x² + x – 7 " .
_____________________________________________
Note:
_____________________________________________
We are given:
_____________________________________________
→ " (7x² + 4x – 6) – (2x² – 3x + 1) " ;
____________________________________
Let us simplify this expression:
____________________________________
Rewrite as:
____________________________________
(7x² + 4x – 6) – 1(2x² – 3x + 1) ;
{Since there is an implied "one", since "1" ; multiplied by any value, results in the same value} ;
___________________________________________
Let us start with the following part of the expression:
___________________________________________
→ " – 1(2x² – 3x + 1) " ;
___________________________________________
Note the "distributive property" of multiplication:
____________________________________________
a(b + c) = ab + ac ;
a(b – c) = ab – ac ;
____________________________________________
As such: " a(b – c + d) = ab – ac + ad " ;
____________________________________________
So:
______________________________________________________
→ " – 1(2x² – 3x + 1) " = (-1 * 2x²) – (-1* -3x) + (-1 * 1) ;
= -2x² – 3x + (-1) ;
= -2x² – 3x – 1 ;
______________________________________________________
Now, bring down the: " 7x² + 4x – 6 " ; and add the " – 2x² – 3x – 1 " ;
as follows:
___________________________________________
→ " 7x² + 4x – 6 – 2x² – 3x – 1 " ;
___________________________________________
→ Combine the "like terms" :
+ 7x² – 2x² = + 5x² ;
+ 4x – 3x = + 1x = + x ;
– 6 – 1 = – 7 ;
____________________________________________
And we can rewrite the simplified expression as:
____________________________________________
→ " 5x² + x – 7 " .
____________________________________________
_____________________________________________
Note:
_____________________________________________
We are given:
_____________________________________________
→ " (7x² + 4x – 6) – (2x² – 3x + 1) " ;
____________________________________
Let us simplify this expression:
____________________________________
Rewrite as:
____________________________________
(7x² + 4x – 6) – 1(2x² – 3x + 1) ;
{Since there is an implied "one", since "1" ; multiplied by any value, results in the same value} ;
___________________________________________
Let us start with the following part of the expression:
___________________________________________
→ " – 1(2x² – 3x + 1) " ;
___________________________________________
Note the "distributive property" of multiplication:
____________________________________________
a(b + c) = ab + ac ;
a(b – c) = ab – ac ;
____________________________________________
As such: " a(b – c + d) = ab – ac + ad " ;
____________________________________________
So:
______________________________________________________
→ " – 1(2x² – 3x + 1) " = (-1 * 2x²) – (-1* -3x) + (-1 * 1) ;
= -2x² – 3x + (-1) ;
= -2x² – 3x – 1 ;
______________________________________________________
Now, bring down the: " 7x² + 4x – 6 " ; and add the " – 2x² – 3x – 1 " ;
as follows:
___________________________________________
→ " 7x² + 4x – 6 – 2x² – 3x – 1 " ;
___________________________________________
→ Combine the "like terms" :
+ 7x² – 2x² = + 5x² ;
+ 4x – 3x = + 1x = + x ;
– 6 – 1 = – 7 ;
____________________________________________
And we can rewrite the simplified expression as:
____________________________________________
→ " 5x² + x – 7 " .
____________________________________________